Isu-Isu Aktual Dalam Al-Qur’an: Ham Dalam Perspektif Al –Quran - Andy Muhammad Ilham Septian; Khusnul Fatimah (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2020)
It was the confusion of secular human rights that prompted Muslim thinkers who joined European Islamic organizations to declare The Universal Islamic Declaration of Human Rights (UIDHR), at the 1980 International Islamic Conference in Paris. However, the declaration of Islamic human rights, which is very similar to secular human rights, also fails at the implementation level. If we return to the Qur'an and hadith, especially the Medina constitution in the context of human rights, there are many verses of the Qur'an which, without going through interpretation, are very in favor of human rights. Human rights principles in the Qur'an can be described in three terms, namely al-istiqrar, namely the right to live on earth until death picks up, al-istimta', namely the right to explore the carrying capacity of life and al-karamah, namely honor. which is identical to each individual but has social implications, because self-respect can only work if there are other people who respect one's human dignity, then al-karamah gives birth to the right of equality.